Memória e história da comunidade de Imbiral: alianças interétnicas constituídas entre indígenas e quilombolas - VAN DEURSEN, Maria Alice Pires Oliveira (2022)
The Dissertation presented here is the result of an investigation into the history and memory of the community of Imbiral Cabeça – Branca, located in the municipality of Pedro do Rosário – MA. For the development of the research, we opted for the qualitative methodology, with bibliographic and documental analysis, we also carried out interviews with community leaders. The questions that arise in this project are related to territoriality, memory, history, and interethnic alliances between Akroá Gamella indigenous people and quilombolas. The Gamella people were considered extinct by anthropologists, indigenists and by FUNAI itself, which, claiming intense miscegenation, started to identify them as “peasants”. However, since 2013, the Gamella have been fighting real battles, suffering several rights violations in the struggle for recognition of their identity and recovery of their territory. The research brings important photographic records that reveal how the Imbiral community incorporates material and immaterial culture in their identity processes. It also presents the results of the investigation into the participation of Gamella indigenous people in one of the most important episodes in the history of Maranhão, known as the Insurrection of Slaves in Viana, which took place in 1867, organized and started by the inhabitants of the São Benedito do Céu Quilombo. Literature about this Revolt, give greater prominence to the protagonism of blacks, the research shows that there was an important participation participation of indigenous people in the insurrection. It was verified, in this study, that the Quilombola Imbiral Cabeça Branca territory has suffered constant violations of its rights, qualified by ILO convention 169 and that its residents are coated with deep vulnerability. Farmers are surrounding the territory and destroying the community's heritage. In addition to the destruction of the geo-environmental diversity of the Legal Amazon in Maranhão, essential for the survival of that community, important places of memory are being destroyed, such as the Cemitério dos Negros. We also found that Imbiral Cabeça-Branca holds a vast and important reserve of quilombola ethnomedicine in Maranhão.